Dependence of the content of starch and reducing sugars on the level of expression of the genes of β-amylases StBAM1 and StBAM9 and the amylase inhibitor StAI during long-term low-temperature storage of potato tubers - A. V. Kulakova; G. I. Efremov; A. V. Shchennikova; E. Z. Kochieva (Вавиловский журнал генетики и селекции)
Solanum tuberosum L. is the most important non-grain starch crop with a potential yield of 38–48 t/ha and a starch content of 13.2–18.7 %. Potato tubers are stored at a low temperature (2–4 °C) in a state of physiological dormancy. A disadvantage of this type of storage is the degradation of starch and the accumulation of reducing sugars (cold-induced sweetening), including due to an increase in the activity of β-amylases that hydrolyze starch to maltose. In this study, a comparative analysis of the β-amylase (StBAM1, StBAM9) and amylase inhibitor (StAI ) gene expression, as well as starch and reducing sugar content in tubers during long-term low-temperature storage (September, February, April) was performed using potato cultivars Nadezhda, Barin, Krasavchik, Severnoe siyanie and Utro. The β-amylase genes, StBAM9 and one of the two StBAM1 homologs (with the highest degree of homology with AtBAM1), were selected based on phylogenetic analysis data. Evaluation of the expression of these genes and the amylase inhibitor gene showed a tendency to decrease in transcription for all analyzed cultivars. The starch content also significantly decreased during tuber storage. The amount of reducing sugars increased in the September–April period, while in February–April, their content did not change (Krasavchik), decreased (Barin, Severnoe siyanie) or continued to grow (Utro, Nadezhda). It can be assumed that the gene activity of StBAM1 and StBAM9 correlates with the amount of starch (positively) and monosaccharides (negatively). The level of StAI expression, in turn, may be directly dependent on the level of StBAM1 expression. At the same time, there is no relationship between the degree of cultivar predisposition to cold-induced sweetening and the expression profile of the StBAM1, StBAM9, and StAI genes.